Hubungan pengetahuan ibu dengan penanganan demam pada anak balita di Gampong Blang Neuang, Kecamatan Beutong, Kabupaten Nagan Raya - Almurdani Almurdani; Erlia Rosita; Ns. Tasnimin; Zakiyah Zakiyah; Rika Andriani (Nur Science Institute, 2026)
Fever in toddlers is common and can lead to complications such as febrile seizures when not managed appropriately; therefore, mothers' knowledge as primary caregivers is a key factor in ensuring accurate fever management at home. This study aimed to examine the association between mothers' knowledge level and fever management practices among toddlers in Gampong Blang Neuang, Beutong Subdistrict, Nagan Raya Regency. A quantitative approach was used with an analytic survey and a cross-sectional design. The sample included 58 respondents selected using accidental (convenience) sampling. Data were collected from May 28 to June 5, 2025, and analyzed using the Chi-square test. The results showed a significant association between mothers' knowledge and toddlers' fever management. These findings underscore the importance of improving mothers' knowledge to help prevent fever-related complications. Therefore, families and village-level health providers should strengthen parent education through counseling sessions or educational meetings on appropriate fever management.